Transcriptome Analysis of Moso Bamboo (Phyllostachys edulis) Reveals Candidate Genes Involved in Response to Dehydration and Cold Stresses - Huang, Zhuo; Zhu, Peilei; Zhong, Xiaojuan; Qiu, Jiarui; Xu, Wenxin; Song, Li (Frontiers in Plant Science, 2022)
Bamboo (Bambusoideae) belongs to the grass family (Poaceae) and has been utilized as one of the most important nontimber forest resources in the world. Moso bamboo (Phyllostachys edulis) is a large woody bamboo with high ecological and economic values. Global climate change brings potential challenges to the normal growth of moso bamboo, and hence its production. Despite the release of moso bamboo genome sequence, the knowledge on genome-wide responses to abiotic stress is still limited. In this study, we generated a transcriptome data set with respect to dehydration and cold responses of moso bamboo using RNA-seq technology. The differentially expressed genes (DEGs) under treatments of dehydration and cold stresses were identified. By combining comprehensive gene ontology (GO) analysis, time-series analysis, and co-expression analysis, candidate genes involved in dehydration and cold responses were identified, which encode abscisic acid (ABA)/water deficit stress (WDS)-induced protein, late embryogenesis abundant (LEA) protein, 9-cis-epoxycarotenoid dioxygenase (NCED), anti-oxidation enzymes, transcription factors, etc. Additionally, we used PeLEA14, a dehydration-induced gene encoding an “atypical” LEA protein, as an example to validate the function of the identified stress-related gene in tolerance to abiotic stresses, such as drought and salt. In this study, we provided a valuable genomic resource for future excavation of key genes involved in abiotic stress responses and genetic improvement of moso bamboo to meet the requirement for environmental resilience and sustainable production.